The Ethics of Downsizing: Perceptions of Rights and Responsibilities - Hopkins, Willie E. (Journal of business ethics, 1999)
Within the context of employee rights and management social responsibility, this paper identifies and explores three ethical dimensions of downsizing. Using ANOVA and Scheffe post-hoc statistical techniques, groups involved in the downsizing decision making process were compared with groups affected by the process on each ethical dimension. Results indicated that those affected by the process attached greater ethical significance to these dimensions than those who were involved in formulating and implementing/communicating downsizing decisions.